Improving the Work Effectiveness of Textile Export Agents in Addressing Operational Barriers: A Qualitative Case Study - Pamela, Maylavalaza; Kustyadji, Gatot; Wardhana, Aditya Narendra; Tutuko, Bambang (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
The decline in textile exports and the increasing complexity of supply chains have intensified operational challenges for small-scale textile export agents. This study aims to identify key operational barriers affecting work effectiveness and to formulate improvement strategies based on practitioners' experiences. A qualitative single-case study was conducted at a privately owned textile export company in Indonesia (Company X). Data were collected through in-depth interviews with two key informants and triangulated with managerial perspectives, limited observation, and document analysis. The data were analyzed using thematic analysis following Braun and Clarke's framework. The findings reveal five interrelated operational barriers: quality inconsistencies and repeated sample revisions; production and delivery delays; weak contractual governance; fragile coordination and communication systems; and psychological pressure arising from export agents' intermediary role. These barriers reduce work effectiveness in terms of quality, speed, dependability, flexibility, and cost. The study proposes three improvement strategies: strengthening contractual governance and sanctions, adopting simple digital systems for coordination and monitoring, and enhancing supplier capacity and quality control, supported by leadership involvement. This study contributes to the governance and coordination literature by highlighting the operational realities of small-scale export agents in developing countries and emphasizing the importance of transitioning from informal, manual practices to structured, digitalized operations.